SWOT-Based Business Model Canvas Analysis as a Tourism Industry Development Strategy for Situ Rawa Gede in Bekasi - Rabhi Fathan Muhammad; Tatik Mulyati; Erik Setya Ramadhan (LP2M IAIN Palopo, 2026)
This study examines the development strategy of Situ Rawa Gede, a community-based urban nature tourism site in Bekasi City, Indonesia. Although it has strong potential as the city’s largest lake and a growing attraction since 2019, the site faces challenges such as limited digital promotion, the absence of a structured masterplan, and broad market segmentation. The research applies a qualitative approach, using interviews with community leaders, SMEs, visitors, and government officials, supported by documentation and observation. The analysis integrates the Business Model Canvas (BMC) with SWOT analysis. The results show that Situ Rawa Gede’s strengths include its natural setting, affordable prices, and the involvement of local SMEs and community groups, while weaknesses relate to limited branding, weak coordination, and reliance on daily visitors. Opportunities lie in government support, demand for eco-education tourism, and digitalization, whereas threats include competition from modern destinations and climate risks. The SWOT suggesting proactive measures such as service digitalization, product diversification, and cross-sector collaboration.